2012
DOI: 10.1093/jac/dks406
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics involved in the occurrence of antibiotic-resistant bacteria: a nationwide multilevel study suggests differences within antibiotic classes

Abstract: Our study suggests differences within antibiotic classes in promoting antibiotic resistance. We identified ceftriaxone, ciprofloxacin and ofloxacin as priority targets in public health strategies designed to reduce antibiotic use and antibiotic-resistant bacteria in French HCFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 37 publications
6
24
0
3
Order By: Relevance
“…Possible or confirmed MDRB infection leads to an increase in antibiotic consumption, which itself increases the selective pressure favouring the most resistant bacteria. Several recent studies have reported an effect of antibiotic use on MDRB emergence both at the national [10] and hospital levels [11,12]. However, it was not possible to control for differences in prescription habits, the infections treated, infection control measures and epidemic phenomena between participating hospital wards in these studies.…”
Section: Introduction Q2mentioning
confidence: 94%
“…Possible or confirmed MDRB infection leads to an increase in antibiotic consumption, which itself increases the selective pressure favouring the most resistant bacteria. Several recent studies have reported an effect of antibiotic use on MDRB emergence both at the national [10] and hospital levels [11,12]. However, it was not possible to control for differences in prescription habits, the infections treated, infection control measures and epidemic phenomena between participating hospital wards in these studies.…”
Section: Introduction Q2mentioning
confidence: 94%
“…Many studies have shown a correlation between antibiotics use and subsequent resistance to antibiotics (22). Because the immunocompromised patients had more frequently received previous antibiotic treatment with b-lactam or fluoroquinolone in the present study, the risk for the development of antibiotic resistance may increase in these patients.…”
Section: Discussionmentioning
confidence: 82%
“…Nem ismert, hogy a nem megfelelő indikáció, a magasabb dózisok, a hosszabb kezelés vagy a terápiaszűkítés hiánya áll-e a magas fluorokinolonfelhasználás hátterében. A fluorokinolonok rezisztenciaindukáló hatása különösen nagy [16][17][18], és hazánkban az invazív izolátumok fluorokinolonrezisztenciája minden vizsgált baktériumtörzs esetén magasabb, mint az euró-pai átlag [19]. Ezenkívül az ECDC legutóbbi pontprevalencia-vizsgálata alapján a Clostridium difficile-fertő-zések hazai aránya rendkívül magas [16], ami mögött részben a magas fluorokinolonhasználat valószínűsíthe-tő.…”
Section: áBraunclassified